RP XVA.1.18-20a - Letters to Emily Evelyn Rathbone from Dorothea Rathbone (née Rankin), London; [1940-1943].
Personal and family news; includes note on informal discussion between Eleanor Rathbone and Nicholas Rathbone on Palestinian affairs (18); news of William Rathbone IX in action with the R.A.F. (19)